Sāhiba srī Gurū Gobinda Siṅgha jī mahārāja jī dī pawitra srī mukhawāka bāṇī dasama srī grantha sāhiba saṭīka wicoṃ srī Jāpu sāhiba saṭīka te srī Akāla usatata saṭīka - Naraiṇa Siṅgha (SAMP early 20th-century Indian books project ;)
Commentary on Jāpu sāhiba and Akāla usatati, compositions by Guru Gobind Singh, 1666-1708.